2014
DOI: 10.3233/bd-130361
|View full text |Cite
|
Sign up to set email alerts
|

Poland's syndrome: A case report with review of literature regarding management

Abstract: This case illustrates the potential benefit of utilizing autologous ALT perforator flap in a girl with Poland's syndrome with a deformed chest wall with hypoplasia of pectoral muscles and absence of the anterior axillary fold which makes positioning of an implant difficult. Breast reconstruction using a microvasular perforator flap is an alternative method to restore the contour of the chest and breast without the use of an implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
7
Order By: Relevance
“…As the most popular perforator flap for postmastectomy breast reconstruction, the DIEP flap is recommended for treating Poland syndrome also because of its ample volume and significantly longer pedicles which allow for more freedom in tissue-tailoring and flap insetting. SGAP [22] and ALT [24, 25] flaps served as alternatives in cases of inadequate abdominal tissue or previous scars. Gautam et al [14]reported the largest series of revision surgeries using perforator flaps for previous implant or flap failure that achieved satisfying long-time results, despite the greater occurrence of short-term complications than with primary reconstructions including hematoma, seroma, and fat necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As the most popular perforator flap for postmastectomy breast reconstruction, the DIEP flap is recommended for treating Poland syndrome also because of its ample volume and significantly longer pedicles which allow for more freedom in tissue-tailoring and flap insetting. SGAP [22] and ALT [24, 25] flaps served as alternatives in cases of inadequate abdominal tissue or previous scars. Gautam et al [14]reported the largest series of revision surgeries using perforator flaps for previous implant or flap failure that achieved satisfying long-time results, despite the greater occurrence of short-term complications than with primary reconstructions including hematoma, seroma, and fat necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе описаны единичные случаи ис-пользования свободных аутотрансплантатов для реконструкции грудной клетки и молочной желе-зы у больных с синдромом Поланда (нижнеяго-дичный и верхнеягодничный лоскуты, лоскут на основе поверхностной нижней эпигастральной артерии, DIEP-лоскут (перфорантный лоскут на основе нижней эпигастральной артерии), сальник, переднелатеральный лоскут бедра, кожно-мышеч-ный лоскут на основе m. gracilis) [33][34][35][36][37]. Недо-статком данных вмешательств является высокий процент осложнений, «плюсами» -незначитель-ный ущерб для донорской области, а также бы-строе восстановление пациентов по сравнению с транспозицией широчайшей мышцы спины [38].…”
Section: реконструктивные вмешательства на грудной клеткеunclassified
“…Однако, по данным A.E. Seyfer et al (2010), ис-пользование силиконовых имплантатов дает боль-шой процент осложнений [16], и, кроме того, при сложных формах синдрома постановка импланта-та крайне затруднительна [36].…”
Section: реконструктивные вмешательства на грудной клеткеunclassified
“…PS [ 7 , 8 ] is a rare congenital anomaly described first in 1897 by Alfred Poland and is characterized by the partial or complete absence of the pectoralis major muscle, ipsilateral symbrachydactyly and is occasionally associated with other malformations of the anterior chest wall and breast.…”
Section: Introductionmentioning
confidence: 99%